Andrea Goulet. Legacies of the Rue Morgue: Science, Space, and Crime Fiction in France. Philadelphia: U of Pennsylvania P, 2016. - Kelsey B. Madsen (Studies in 20th & 21st Century Literature, 2018)
Review of Andrea Goulet. Legacies of the Rue Morgue: Science, Space, and Crime Fiction in France. Philadelphia: U of Pennsylvania P, 2016. 295pp.
Keywords: Genre Studies; Detective Novel; Crime Fiction; Science; Geography